KNOWLEDGE TRANSFER THROUGH NEWHEXA’S CULTURAL STORYTELLING IN INDONESIA’S HYDRATION ECONOMY BATTLEFIELD AS A PEDAGOGICAL MODEL IN ENTREPRENEURSHIP EDUCATION - Robimadin, Cahya Nugeraha; Suryadi, Nanang; Handrito, Radityo Putro (UNIVERSITAS NEGERI SURABAYA, 2025)
Intense competition in Indonesia’s Packaged Drinking Water (AMDK) industry necessitates entrepreneurial strategies emphasizing innovation and communication. This study examines how product innovation and marketing communication influence repurchase intention, mediated by brand image, using NEWHEXA (East Java) as a case study. A quantitative approach employing SEM-PLS analysis of 200 active consumers yielded key findings: (1) Innovation (β = 0.35, p < 0.001) and marketing communication (β = 0.41, p < 0.001) significantly enhance brand image; (2) Brand image exerts the strongest direct impact on repurchase intention (β = 0.62, p < 0.001); (3) Brand image significantly mediates the relationship (VAF = 58.3%), confirming its pivotal causal role. These findings have strong implications for entrepreneurship curricula that emphasize cultural storytelling as a strategy to foster consumer loyalty. They strongly support integrating packaged water industry case studies, like NEWHEXA, into entrepreneurship curricula, particularly modules using cultural storytelling to build consumer loyalty through authentic brand identity. Key limitations include geographically focused sampling and respondent homogeneity. Future research should investigate socio-cultural moderators and the socio-economic impact of AMDK innovations on SMEs.